Terapi Bermain Untuk Meningkatkan Keterampilan Motorik Kasar Dan Motorik Halus Pada Anak Tuna Rungu - Utami, Eliza Sutri (Institut Agama Islam Sumatera Barat Pariaman, 2024)
Some special needs children, such as the deaf, may have underdeveloped motor skills. This condition impacts their daily activities as well as academic performance. Play therapy is an intervention applied in this study to enhance both gross and fine motor skills in 1st-grade students. The play therapy in this study consists of 17 sessions (60 minutes/session). Data collection involves observation, interviews with relevant parties, and visual motor integration tests. The research design employs qualitative descriptive with a case study approach. This study involves one subject, an 8-year-old 1st-grade student in a special education class. Data analysis technique utilizes qualitative data analysis. The results indicate that play therapy can improve both gross and fine motor skills in deaf children of Elementary School.